ON THE USE OF COMBINED GEOPHYSICAL METHODS TO ASSESS WATER CONTENT AND WATER CONDUCTIVITY OF NEAR-SURFACE FORMATIONS - Garambois S.; Senechal P.; Perroud H. (My University, 2002)
We propose to deepen the interpretation of combined geophysical methods (georadar, seismic and electric) to assess physical properties characterizing the near-surface porous formations, especially the influence of water. Velocity analysis of multioffset georadar data are used together with seismic methods to estimate lateral and vertical ground water fluctuations. This enables us to identify transitions from non-saturated to fully saturated porous layers with certainty. Furthermore, the accurate knowledge of seismic velocities helps to estimate the porosity of the ground water formations. Finally, we show how the radar technique may be useful in solving the problem of trade-off between bulk resistivity, which is deduced from electrical measurements, and that of water ionic conductivity and water content. These theoretical considerations are illustrated using various measurements conducted at the same test site. Our interpretation is compared with a few laboratory measurements on water and soil samples. This study displays the impact of combined geophysical approaches for providing models of water and ionic transfers down to a depth of several metres.
Keywords: GROUND PENETRATING RADAR; SEISMIC AND ELECTRICAL METHODS; WATER CONTENT; WATER CONDUCTIVITY